ProBiotea biscuits: a probiotic delight for all ages / Nur Insyirah Nurman ... [et al.] - Nurman, Nur Insyirah; Salehudin, Farisya Syazwena; Azhari, Nurul Ainnah Farhanah; Zulkarnain, Nur Emely Sofea; Abdullah, Noraini (2024)
Brief description of the business and product concepts: We are introducing ProBiotea Biscuits which represent an innovative and health-conscious addition to the snack to replace supplements, combining the delightful experience of biscuit consumption with the numerous benefits of probiotics. Designed to cater to all age groups, we focus on providing a tasty and convenient way for consumers to incorporate probiotics into their daily diets. The global demand for functional foods, especially those promoting gut health, has witnessed a significant surge. ProBiotea Biscuits aims to tap into this growing market by offering a convenient and palatable solution for individuals seeking a tasty snack that also supports their digestive well-being. With an increasing awareness of the importance of gut health across demographics, our product addresses a broad and expanding consumer base. The target market and projections: Based on the product, our target market is made up of all age groups such as children, young adults, adults, and seniors who all have some digestive problems that may lead to constipation, diarrhea, and obesity. Also, Young adults are looking to enhance their beauty and lose weight, it's crucial to approach these goals healthily and sustainably like taking a probiotic biscuit. Furthermore, senior citizens can strengthen their immune systems since their immune system often may be weakened by poor dietary habits and a lack of vital nutrients, making it more likely to get an illness or infection and it can be remedied by consuming probiotics. This product is also suitable for people who have eczema or are allergic to biscuits. People can get many benefits from this ProBioTea biscuit for their health.